"Do as we say, not as we do?" the lifestyle behaviours of hospital doctors working in Ireland: a national cross-sectional study - Anthony O' Keeffe; Blánaid Hayes; Lucia Prihodova (BMC, 2019)
Abstract Background This study was conducted to assess the lifestyle behaviours of a national sample of hospital doctors working in Ireland. We also sought to compare the prevalence of these behaviours in doctors to the general Irish population. Methods This was a national cross-sectional study of a randomised sample of hospital doctors working in Irish publicly funded hospitals and residential institutions. The final cohort consisted of 1749 doctors (response rate of 55%). All hospital specialties were represented except radiology. The following data were collected: sociodemographic data (age, sex), work grade (consultant, trainee) average hours worked over a two-week period, specialty and lifestyle behaviours (smoking, alcohol, physical activity). Lifestyle data for the general population was provided by the Healthy Ireland 2015 study. Results Half of participants were men (50.5%). Just over half of the sample were consultants (54.3%), with 45.7% being trainees. 9.3% of doctors surveyed were smokers, 88.4% consumed alcohol and 24.5% were physically inactive. Trainees were more likely to smoke and be physically inactive when compared to consultants. Smoking rates amongst doctors were lower than the general population (9.3% -v- 23%). Doctors were more likely to consume alcohol than the general population (88.4% -v- 71.7%) but less likely to engage in binge drinking on a typical drinking occasion (12.8% -v- 39.5%). Doctors were more compliant than the general population with minimum exercise targets (75.5% -v- 70.5%), but less likely to engage in health enhancing physical activity (19.1% -v- 33%). Conclusions While the prevalence of health behaviours amongst hospital doctors in Ireland compares favourably to the general population, their alcohol consumption and engagement in health enhancing physical activity suggest room for improvement. Continued health promotion and education on the importance of personal health behaviours is essential.